Production of Α-amylase from haloarcula hispanica 2TK2 strain: Optimization of the parameters that effecting activity - (:unkn) unknown (My University, 2013)
Halophilic archaea adapted to life at salt concentrations at or nearly saturation and haloarchaeal proteins have specific properties for adapting to highly salty environments, so that their proteins maintain stability and functionality in extreme habitats. Extracellular enzymes of halophiles are always exposed to high salt must have unique amino acid properties. Many haloarchaeal enzymes have been detected in halophiles; one of them is Α-amylase that is industrially very important. In this study, we investigated the Α-amylase properties of Haloarcula hispanica 2TK2 strain isolated from Tuzkoy Salt Mine of Turkey. The Α-amylase activity was studied in 25-75 °C, 3-6 M salt concentrations and at pH 4-8. The optimum pH, temperature and NaCl concentration for the relative activity were determined as 6.9, 52 °C and 5 M, respectively. It was also found that the relative activity increases while salt concentration of growth media increases, in all samples. Also, the presence of starch in growth media significantly increased the activity of secreted Α-amylase from the halophilic archaeon Haloarcula hispanica 2TK2. This study indicates that Α-amylase from Haloarcula hispanica 2TK2 is found to be salt tolerant. Thus, it may be considered a potential candidate for future use in industrial processes which require enzyme activity at high salt concentrations.
Keywords: Α-amylase; Enzyme activity; Haloarcula hispanica 2TK2; Salt tolerancy